Study on immune function monitoring during altitude training for adolescent athletes - Gan, C.; Guizhou, J. Z.; Qiu, X.; Zong, L. (Exercise Biochemistry Review, 2018)
Objective Monitoring the changes of the body's immune function during altitude training is of great significance for understanding the athlete's physical function and judging the degree of fatigue. In this paper, the immune function of adolescent athletes in sports training in different altitudes was monitored, and the effects of different altitude training on immunoglobulins and T lymphocytes and their subgroups in adolescent athletes were discussed.